2012
DOI: 10.1371/journal.pone.0031066
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Luteolin Inhibits Fcγ-Dependent Respiratory Burst in Granulocytes, but Not Skin Blistering in a New Model of Pemphigoid in Adult Mice

Abstract: Bullous pemphigoid is an autoimmune blistering skin disease associated with autoantibodies against the dermal-epidermal junction. Passive transfer of antibodies against BP180/collagen (C) XVII, a major hemidesmosomal pemphigoid antigen, into neonatal mice results in dermal-epidermal separation upon applying gentle pressure to their skin, but not in spontaneous skin blistering. In addition, this neonatal mouse model precludes treatment and observation of diseased animals beyond 2–3 days. Therefore, in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…In addition, they recruited murine leukocytes and induced skin blistering thus reproducing the human BP at the clinical, immunological and histopathological levels. These findings are in line with similar results of inflammatory blistering in another newly developed passive antibody transfer model of pemphigoid disease in which we pre-immunized adult mice with rabbit IgG followed by injection of collagen XVII-specific rabbit IgG [43]. While having the advantage of an increased inflammatory reaction and more extensive disease in mice compared with the mouse model presented here, the model reported by Oswald et al , has some limitations due to the active immunization with the rabbit IgG, which pose constraints for designing studies addressing the pathophysiology of the pemphigoid disease in patients.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, they recruited murine leukocytes and induced skin blistering thus reproducing the human BP at the clinical, immunological and histopathological levels. These findings are in line with similar results of inflammatory blistering in another newly developed passive antibody transfer model of pemphigoid disease in which we pre-immunized adult mice with rabbit IgG followed by injection of collagen XVII-specific rabbit IgG [43]. While having the advantage of an increased inflammatory reaction and more extensive disease in mice compared with the mouse model presented here, the model reported by Oswald et al , has some limitations due to the active immunization with the rabbit IgG, which pose constraints for designing studies addressing the pathophysiology of the pemphigoid disease in patients.…”
Section: Discussionsupporting
confidence: 86%
“…To model both the initiation phase and the effector phase of these diseases, models in adult animals relying on extensive immunization with BP180 or collagen VII have been established. In the immunization models, neutrophil depletion is partially effective in reducing disease [85]. Interestingly, in the immunization-induced EBA model, chronic depletion of neutrophils (or use of GM-CSF knockout mice) leads to reduced autoantibody titers, with reduced skin inflammation [86].…”
Section: Neutrophils In Dermatologic Disease Modelsmentioning
confidence: 99%
“…Animal model studies showed the critical role of autoimmune complexes in triggering the inflammatory process leading to the DEJ disruption and subsequently to blister formation (Liu et al 1993)(Hirose et al 2011)(Oswald et al 2012). …”
Section: Introductionmentioning
confidence: 99%